2013
DOI: 10.1016/j.vaccine.2013.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Avian metapneumoviruses expressing Infectious Bronchitis virus genes are stable and induce protection

Abstract: The study investigates the ability of subtype A Avian metapneumovirus (AMPV) to accept foreign genes and be used as a vector for delivery of Infectious bronchitis virus (IBV) QX genes to chickens. Initially the GFP gene was added to AMPV at all gene junctions in conjunction with the development of cassetted full length DNA AMPV copies. After recombinant virus had been recovered by reverse genetics, GFP positions supporting gene expression while maintaining virus viability in vitro, were determined. Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Tokusumi et al have shown in a study where they inserted the sequence encoding for secreted alkaline phosphatase into all possible genome positions that this seems to be the case for Sendai virus (Tokusumi et al, 2002). Also, this idea is further supported by other studies in paramyxoviruses comparing different insertion positions (Falchieri et al, 2013; von Messling et al, 2004; Zhao and Peeters, 2003). However, in a study with recombinant VSV, where the authors inserted a 661 nucleotide long non-coding ATU at each of the gene-junctions, the authors only observed a strong attenuation when the ATU was inserted between the N and P gene (first gene junction), and no attenuation in vitro when any of the other gene junctions were used (Wertz et al, 2002).…”
Section: Challenges In the Development And Application Of Reportersupporting
confidence: 65%
“…Tokusumi et al have shown in a study where they inserted the sequence encoding for secreted alkaline phosphatase into all possible genome positions that this seems to be the case for Sendai virus (Tokusumi et al, 2002). Also, this idea is further supported by other studies in paramyxoviruses comparing different insertion positions (Falchieri et al, 2013; von Messling et al, 2004; Zhao and Peeters, 2003). However, in a study with recombinant VSV, where the authors inserted a 661 nucleotide long non-coding ATU at each of the gene-junctions, the authors only observed a strong attenuation when the ATU was inserted between the N and P gene (first gene junction), and no attenuation in vitro when any of the other gene junctions were used (Wertz et al, 2002).…”
Section: Challenges In the Development And Application Of Reportersupporting
confidence: 65%
“…Vaccine persistence, circulation and reversion to virulence have also been frequently reported for other empirically attenuated avian vaccines developed to control immunosuppressive or respiratory diseases [ 52 , 53 , 54 ]. Next-generation vaccines, with improved stability and safety, are currently under study and development for most avian pathogens and, in the future, they will likely replace traditional vaccines [ 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to develop a novel bivalent vaccine protect against NDV and IBV. In recent decades, attempts have been made to develop recombinant vaccines using NDV [48][49][50], adenovirus [51], duck enteritis virus [52], and avian metapneumovirus [53] viral backbones expressing the S1 or S2 portion of the IBV spike gene with differing levels of protection from IBV challenge. Among them, the NDV vector shows great promise due to its excellent characteristics, such as rapid and long-lasting immune response, low production costs, convenience of administration, and genetic stability [45].…”
Section: Discussionmentioning
confidence: 99%